2021
DOI: 10.18240/ijo.2021.05.03
|View full text |Cite
|
Sign up to set email alerts
|

Protective effects of upregulated HO-1 gene against the apoptosis of human retinal pigment epithelial cells in vitro

Abstract: AIM: To investigate the protective effect of heme oxygenase-1 (HO-1) against H2O2-induced apoptosis in human ARPE-19 cells. METHODS: The lentiviral vector expressing HO-1 was prepared and transfected into apoptotic ARPE-19 cells induced by H2O2. Functional experiments including cell counting kit-8 (CCK-8) assay, flow cytometry (FCM) and mitochondrial membrane potential assay were conducted. RESULTS: The ultrastructure of ARPE-19 cells was observed using transmission electron microscope (TEM). It was found that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…This is in good agreement with the results of previous studies ( Zhao et al, 2019 ; Rodius et al, 2020 ; Molagoda et al, 2021 ; Ding et al, 2022 ) and suggests that fisetin may act as an oxidative stress blocker. Several previous studies have proven that oxidative stress-induced apoptosis by H 2 O 2 treatment in ARPE-19 cells is directly correlated with mitochondrial impairment ( Zhao et al, 2020 ; Hong et al, 2021b ; Kim et al, 2021b ). Alteration of the outer mitochondrial membrane permeability by oxidative damage is linked to MMP dissipation.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…This is in good agreement with the results of previous studies ( Zhao et al, 2019 ; Rodius et al, 2020 ; Molagoda et al, 2021 ; Ding et al, 2022 ) and suggests that fisetin may act as an oxidative stress blocker. Several previous studies have proven that oxidative stress-induced apoptosis by H 2 O 2 treatment in ARPE-19 cells is directly correlated with mitochondrial impairment ( Zhao et al, 2020 ; Hong et al, 2021b ; Kim et al, 2021b ). Alteration of the outer mitochondrial membrane permeability by oxidative damage is linked to MMP dissipation.…”
Section: Discussionmentioning
confidence: 99%
“…For example, it has been reported that negative regulation of Nrf2 is implicated in the pathogenesis of maculopathy ( Datta et al, 2017 ; Bellezza, 2018 ; Hyttinen et al, 2019 ), and mice deficient in Nrf2 have been shown to exhibit retinal alterations similar to AMD ( Zhao et al, 2014 ; Rowan et al, 2020 ). On the other hand, Nrf2-mediated activation of HO-1 was effective in ameliorating oxidative damage in human RPE cells ( Lambros and Plafker, 2016 ; Hyttinen et al, 2019 ; Hong et al, 2021b ). In the meantime, many previous results have demonstrated that activation of HO-1 by some phytochemicals with antioxidant activity plays an important role in the resistance of ARPE-19 cells to oxidative stress ( Zhao et al, 2020 ; Chen et al, 2021 ; Zhang et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations